Conducting system of the winter wheat flag leaf under conditions of simulated drought - V. L. Gaze; N. V. Yanovskaya; I. A. Lobunskaya; P. I. Kostylev; D. M. Marchenko (Зерновое хозяйство России)
The current paper has presented data on the study of the flag leaf conducting system of winter wheat grown under drought in the period of 2018–2020. The objects of the study were 10 winter wheat varieties, developed by the researchers of the FSBSI «ARC «Donskoy». The purpose of the work was to study the influence of the development degree of the leaf conducting system of winter wheat under conditions of simulated drought on productivity and 1000-grain weight. When studying samples under conditions of simulated drought, there were obtained data on the development of the leaf conducting system (number and total area of vascular bundles). As a result of the study, there was established that when developing under conditions of insufficient moisture supply, the varieties ‘Etyud’, ‘Zodiak’, ‘Asket’, ‘Zhavoronok’ and ‘Ermak’ had the maximum number of vascular bundles in the leaves and a minimum decrease of the triat ‘1000-grain weight’ and productivity in relation to optimal growing conditions. The identified samples had the following indicators: the variety ‘Etyud’ (47 pieces, on 9.2 and 27.3%), the variety ‘Zodiak’ (53 pieces, on 10.5 and 30.5%), the variety ‘Ascetik’ (51 pieces, on 11.7 and 31.1%), the variety ‘Zhavoronok’ (49 pcs., on 12.6% and 27.5%) and the variety ‘Yermak’ (50 pcs., on 12.6% and 30.8%), respectively, which indicates the drought resistance of the varieties. There has been found a strong and medium positive correlation between the traits ‘number of bunches’ and ‘1000-grain weight’ (r=0.74) with productivity (r=0.68). A powerful leaf conducting system in arid conditions was determined in the varieties ‘Yubiley Dona’ (13.080 µm²), ‘Podarok Krymu’ (11.339 µm²), ‘Etyud’ (11.003 µm²), ‘Zodiak’ (10.907 µm²), ‘Premiera’ (10.560 µm²), which are able to provide emerging grains with a sufficient quantity of organic substances.